Histopathological diagnosis of tumour deposits in colorectal cancer: a Delphi consensus study. Issue 2 (17th May 2021) - Lord, Amy; Brown, Gina; Abulafi, Muti; Bateman, Adrian; Frankel, Wendy; Goldin, Robert; Gopal, Purva; Kirsch, Richard; Loughrey, Maurice B; Märkl, Bruno; Moran, Brendan; Puppa, Giacomo; et al.
Abstract : Aims: Tumour deposits (TDs) are an important prognostic marker in colorectal cancer. However, the classification, and inclusion in staging, of TDs has changed significantly in each tumour–node–metastasis (TNM) edition since their initial description in TNM‐5, and terminology remains controversial. Expert consensus is needed to guide the future direction of precision staging. Methods and results: A modified Delphi consensus process was used. Statements were formulated and sent to participants as an online survey. Participants were asked to rate their agreement with each statement on a five‐point Likert scale and also to suggest additional statements for discussion. These responses were circulated together with anonymised comments, and statements were modified prior to carrying out a second online round. Consensus was set at 70%. Overall, 32 statements reached consensus. There were concerns that TDs were currently incorrectly placed in the TNM system and that their prognostic importance was being underestimated. There were concerns regarding interobserver variation and it was felt that a clearer, more reproducible definition of TDs was needed. Conclusions: Our main recommendations are that the number of TDs should be recorded even if lymph node metastases (LNMs) are also present and that nodules with evidence of origin [extramural venous invasion (EMVI), perineural invasion (PNI), lymphatic invasion (LI)] should still be categorised as TDs and not excluded, as TNM‐8 specifies. Whether TDs should continue to be included in the N category at all is controversial, and did not achieve consensus; however, participants agreed that TDs are prognostically worse than LNMs and the N1c category is suboptimal, as it does not reflect this. Abstract :